Evaluation of service area and ease of access to public hospitals in Riyadh using GIS - Al-Adhyani, Sahoud Rahim (Journal of Humanities & Social Sciences, 2023)
This research aims to evaluate the service ranges of the hospital and the ease of access to it and to know the extent of the city's need to expand the number of public hospitals and propose the appropriate place for them, and within the GIS environment, service area analysis models were used with a standard of (20) km and a time distance for three time periods (5-10-15) minutes to reach the hospital and model the site - allocation - for a response time of (15) minutes and measure the shortest distance to reach public hospitals for the shortest distance within a time range (15) minutes available within the network analyzer tools in the ArcMap program to evaluate The current situation, and the study of the expansion of the health service of public hospitals. The results of the study showed the different spatial distribution of hospitals and as a result came a number (16) neighborhood of the city of Riyadh outside the scope of the geographical service of public hospitals and that (17) neighborhood of the city of Riyadh cannot residents of (188,414) people access to public hospitals within (15) minutes and constitute (11%) of the total population of the city of Riyadh and after the application of the analysis of the shortest distance between neighborhood centers and public hospitals found that (74) neighborhood center in the city of Riyadh patients cannot reach To the nearest public hospital in less than or equal to (15 minutes) and they have to cover longer distances, up to (40 km) in some neighborhoods, and a longer time of up to (26 minutes) on the road at its maximum speed.
Keywords: hospital; geographical coverage; allocation; spatial distribution; road